Serum KL-6 as a Candidate Predictor of Outcome in Patients with SARS-CoV-2 Pneumonia - Kattner, Simone; Sutharsan, Sivagurunathan; Berger, Marc Moritz; Limmer, Andreas; Jehn, Lutz Bernhard; Herbstreit, Frank; Brenner, Thorsten; Taube, Christian; Bonella, Francesco (Journal of Clinical Medicine, 2023)
Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2)-infection is associated with an extremely variable disease course. When interstitial pneumonia (IP) occurs, it can lead to acute respiratory distress syndrome and death. Serum Krebs von den Lungen-6 (KL-6) is an established marker of IP, but its role as a marker of SARS-CoV-2 pneumonia is debated. This bicentric study included 157 patients with SARS-CoV-2 pneumonia. The WHO Ordinal Scale for Clinical Improvement (0–10 points) was used to classify the clinical course. Serum samples were collected at admission, and on days 3 and 7 of hospitalization. KL-6 was measured by using automated chemiluminescence immunoassay. A total of 68 patients developed a severe SARS-CoV-2 pneumonia, 135 of them required oxygen, and 15 died during hospitalization. The patients requiring non-invasive ventilation, invasive ventilation, or extracorporeal membrane oxygenation had significantly higher serum KL-6 levels at admission. The serum KL-6 levels were tendentially higher in patients who died than in those who survived. Logistic regression identified serum KL-6 at a cut-off of 335 U/mL at admission as a significant predictor of severe SARS-CoV-2 pneumonia outcome. Serum KL-6 seems to be a candidate biomarker for the clinical routine to stratify patients with SARS-CoV-2 pneumonia for the risk of a severe disease outcome or death.
CRIS-Team Scopus Importer:2023-11-24
Keywords: biomarker; COVID-19; disease outcome; KL-6; SARS-CoV-2 pneumonia